REVITALIZING PUBLIC SPACES AND EDUCATING CHILDREN THROUGH VISUAL COMMUNICATION IN KALISAMPURNO VILLAGE - Fikri, M. Andi; Istiqomah, Istiqomah (Journal of Social Comunity Services, 2025)
Objective: This study aims to revitalize public spaces and strengthen early childhood education through a visual communication approach in Kalisampurno Village, Tanggulangin District, Sidoarjo Regency. The activity focused on utilizing Kalisampurno Dam Park as a multifunctional public space that can accommodate social interaction, education, and strengthen the village's visual identity. Method: The community-based participatory approach was used, with an implementation strategy in the form of project-based learning. This activity involved 39 Communication Science students from Muhammadiyah University of Sidoarjo who were divided into three divisions: quote boards, education, and games. The data collection process was carried out through participatory observation, informal interviews, and visual documentation, then analyzed descriptively qualitatively. Results: The results of the program showed that the revitalization of public spaces through aesthetic elements (quote boards, garden decorations, welcoming monuments) successfully strengthened the park's image as an educational and tourist destination. The "Learning While Playing" program also succeeded in involving local PAUD institutions in culturally based outdoor educational activities. These findings indicate that locally based visual communication can be an effective tool in supporting character education and cultural preservation. Novelty: This program's novelty lies in the integration of public art, early childhood education, and cross-community collaboration in a single model of sustainable service.